DARI IDE KE AKSI; MANAJEMEN ORGANISASI UNTUK PELAKU EKONOMI KREATIF - Rosalinda Septiani Sitompul; Delviana Romauli Wanti Sihombing; Joan Berlin Damanik; Niarita Bukit; Jeriston Habayahan; Yesika Angelina Tamba; Listia Sri Hati Panjaitan (Smart Education, 2025)
Abstract: Community service by the Management Study Program of the Faculty of Economics, Universitas Sisingamangaraja XII Tapanuli, in Matiti 2 Village, Dolok Sanggul, which aims to strengthen community-based creative economy through the guidance of the Baion Craftsmen Group 'Setia'. The main issue is the need to strengthen the capacity of artisan groups to face the challenges of a creative economy based on local wisdom, such as access to capital, digitalization, marketing, and product legality. The methods used include continuous training, managerial mentoring, the contextual application of POAC management, as well as strengthening networks and transforming organizational paradigms towards a collaborative and adaptive model. The innovation process is carried out from local inspiration to digital marketing, while continuous evaluation and intellectual property protection serve as key pillars. The results of the activities show increased independence and competitiveness of artisan groups, the emergence of flagship products, and the formation of SME embryos that are oriented toward inclusive growth and cultural preservation. In conclusion, a community-based creative economy approach is effective in driving village economic growth as long as it is supported by adaptive management, technology integration, multi-stakeholder synergy, and continuous innovation cycles.Â Keywords : baion; creative economy; UMKMÂ Abstrak: Pengabdian kepada masyarakat Prodi Manajemen Fakultas Ekonomi Universitas Sisingamangaraja XII Tapanuli di Desa Matiti 2 Dolok Sanggul yang bertujuan memperkuat ekonomi kreatif berbasis komunitas melalui pembinaan Kelompok Pengrajin Baion â€œSetiaâ€. Permasalahan utama adalah perlunya penguatan kapasitas kelompok pengrajin untuk menghadapi tantangan ekonomi kreatif berbasis kearifan lokal, seperti akses modal, digitalisasi, pemasaran, dan legalitas produk. Metode yang digunakan meliputi pelatihan berkelanjutan, pendampingan manajerial, penerapan manajemen POAC secara kontekstual, serta penguatan jejaring dan transformasi paradigma organisasi menuju model yang kolaboratif dan adaptif. Proses inovasi dilakukan dari inspirasi lokal hingga digitalisasi pemasaran, sementara evaluasi berkelanjutan dan perlindungan hak kekayaan intelektual menjadi pilar utama. Hasil kegiatan menunjukkan meningkatnya kemandirian dan daya saing kelompok pengrajin, lahirnya produk unggulan, serta terbentuknya embrio UMKM yang berorientasi pertumbuhan inklusif dan pelestarian budaya. Kesimpulannya, pendekatan ekonomi kreatif berbasis komunitas efektif mendorong pertumbuhan ekonomi desa asalkan didukung manajemen adaptif, integrasi teknologi, sinergi multi-pihak, dan siklus inovasi berkelanjutan.Â Kata Kunci : baion; ekonomi kreatif; UMKM